Pengaruh Motivasi dan Kemandirian Belajar Peserta Didik Terhadap Prestasi Belajar Matematika di Sekolah Dasar - Mua’mar Mua’mar; M. Agus Purnomo; Winda Febriani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Motivation and learning independence are important things in improving students' learning achievement, especially in mathematics. Good motivation and independence will foster a sense of enthusiasm in students' independent learning so that superior learning achievements are created in accordance with the goals to be achieved. This article aims to determine the effect of motivation and independence on students' learning achievement on students' mathematics content. This quantitative correlation research was conducted as a case study of fifth grade elementary school students and the purpose of this study was to describe the level of influence of students' motivation and independence on mathematics learning achievement. There are a total of 26 students of class v Elementary School from SDN Keboledan 02 sub-district Wanasari, Brebes which are sampled in this study. The data were collected through a questionnaire or questionnaire from the motivation variable, independence variable and the results of the final semester assessment (PAS) of students. The results of the data processed through statistical calculations obtained through the use of SPSS 22 . The data shows that there is an influence between motivation on student learning achievement and the influence of independence on student learning achievement.